ASPECTE COMPARATIVE PRIVIND INFRACTIUNEA CONTINUATA, INFRACTIUNEA DE OBICEI SI CONCURSUL REAL OMOGEN DE INFRACTIUNI - Monica Pocora (EIRP Proceedings, 2008)
In criminal law, the notion of "crime" means a fundamental institution, whose analysis isvery extensive. The phrase "crime unit" designates the unique entity, when an activity in fact is reported to asingle basis of assessment and determine a single content of incrimination.“Plurality of crime” means the reporting of the same activity in fact to the same basis of assessment, but in thiscase is determined the incrimination content of more facts.Both the unit and the plurality of crimes have more subgroups, which although are different, they havealso common aspects. As regarding to the crime unit, we can list the simply unit of crime, crime continues, crimedisorders, continued, complex, progressive and usually crime. From the plurality of crime, we can list thecontest of crimes and crime relapse.In regard of similarities and differences, we can talk about the similarities between continued crimeand homogeneity real contest, evenly between continued crime and usually crime, the complex crime andheterogeneous real contest, progressive crime and continue permanently crime. Thus, in this paper I’vepresented the differences and similarities between continued crime, homogeneity real contest and usually crime.